2016
DOI: 10.1016/j.ijfoodmicro.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and predicting growth of psychrotolerant pseudomonads in milk and cottage cheese

Abstract: Document Version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The findings are comparable with those of other studies; for example, on average, about 83% of Listeria monocytogenes and 75% of LAB observed in cottage cheese were within the ASZ [35]; and 78% of measured psychrotolerant pseudomonads in milk and cottage cheese lied in the ASZ [33].…”
Section: Validation Of the Kinetics Models In Dynamic Temperaturesupporting
confidence: 90%
See 2 more Smart Citations
“…The findings are comparable with those of other studies; for example, on average, about 83% of Listeria monocytogenes and 75% of LAB observed in cottage cheese were within the ASZ [35]; and 78% of measured psychrotolerant pseudomonads in milk and cottage cheese lied in the ASZ [33].…”
Section: Validation Of the Kinetics Models In Dynamic Temperaturesupporting
confidence: 90%
“…The above results indicate that the developed kinetics models were acceptable for further application in prediction of TVC and Pseudomonas growth in Pangasius fillets at low temperatures, since more than 70% of the observed counts were within the ASZ [33][34][35][36].…”
Section: Validation Of the Kinetics Models In Dynamic Temperaturementioning
confidence: 74%
See 1 more Smart Citation
“…The former is the well-known Baranyi and Roberts model (1994) [Eq. 1] and the latter is the equation of Martinez-Rios et al (2016) [Eq. 2] for calculating the growth rate as function of environmental parameters (Temperature, pH and AW) for Pseudomonads.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of lactic, acetic and citric acid were determined by HPLC using external standards for identification and quantification. In order to improve extraction, a centrifugation step was applied (Dalgaard and Jørgensen, 2000;Martinez-Rios et al, 2016). Phosphate and citrate salt concentrations were determined by Eurofins, New Orleans, USA (test method QA02S).…”
Section: Accepted Manuscriptmentioning
confidence: 99%